2011
DOI: 10.1177/1741659011412124
|View full text |Cite
|
Sign up to set email alerts
|

Loverboys in the Amsterdam Red Light District: A realist approach to the study of a moral panic

Abstract: In the Netherlands the English word 'loverboys' describes pimps who use their seductive skills to exploit young girls as prostitutes. Public interest and concern has been enormous. But no images of or interviews with loverboys have appeared in the media. This article examines the 10-year-long history of the phenomenon as a classic moral panic constructed by the media, social workers and politicians. Our analysis also seeks to get behind the media representations, using discovery research methods from urban eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…A more measured report by the criminologist Bovenkerk and colleagues concluded that loverboys were a modern incarnation of the traditional pimp and that the phenomenon had been overstated. However, the report also concluded that the legalisation of brothels had not eradicated pimping from the licensed sector (Bovenkerk et al, 2006). By 2005 a veritable media industry had emerged around the issue of prostitution.…”
Section: The Return To (Semi-)prohibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more measured report by the criminologist Bovenkerk and colleagues concluded that loverboys were a modern incarnation of the traditional pimp and that the phenomenon had been overstated. However, the report also concluded that the legalisation of brothels had not eradicated pimping from the licensed sector (Bovenkerk et al, 2006). By 2005 a veritable media industry had emerged around the issue of prostitution.…”
Section: The Return To (Semi-)prohibitionmentioning
confidence: 99%
“…A bestselling book by one of the alleged victims (Mosterd, 2008) turned the loverboy phenomenon into a national moral panic, and many schools and welfare agencies started campaigns to warn young girls for the dangers of loverboys. A research study by a leading Dutch criminologist (Bovenkerk et al, 2006) concluded that the loverboys were a contemporary version of ordinary pimps and that the phenomenon was probably not as widespread as suggested. When the Mosterd book turned out to be a hoax, the loverboy panic subsided somewhat.…”
Section: The Repressive Turnmentioning
confidence: 99%
“…Other girls entered into a business relationship with a young man and subsequently went on to work as prostitutes (see for research on relationships between pimps and prostitutes in Amsterdam and in particular business relationships also [21]: 42-49, 160-161). In short, there are many variations to the stereotypical story about loverboys that are constantly being repeated in the media (see [3]). Some instances of behaviour consistent with the stereotype of the loverboy appeared to have been inspired by either the popular media or the example of other more successful pimps.…”
Section: Imitating the Pimp And Ho Culturementioning
confidence: 99%
“…Regardless of the diverse ethnic origins of both perpetrators and victims, public opinion is mainly concerned with Moroccan (or Antillean) perpetrators overpowering white, innocent girls with their charms in order to exploit them ruthlessly [2,3]. The popular music of famous rappers and the violent and promiscuous youth culture coming from the American ghettos to the Netherlands via the media have created an atmosphere where the sons of immigrants feel justified to 'make their move'.…”
Section: Imitating the Pimp And Ho Culturementioning
confidence: 99%
See 1 more Smart Citation